Laser‐Mediated Microlesions in Mouse Neocortex to Investigate Neuronal Degeneration and Regeneration. Issue 1 (1st October 2015) - Jackson, Johanna; Canty, Alison J.; Huang, Lieven; De Paola, Vincenzo
Abstract: In vivo two‐photon (2P) imaging enables neural circuitry to be repeatedly visualized in both normal conditions and following trauma. This protocol describes how laser‐mediated neuronal microlesions can be created in the cerebral cortex using an ultrafast laser without causing a significant inflammatory reaction or compromising the blood‐brain barrier. Furthermore, directives are provided for the acute and chronic in vivo imaging of the lesion site, as well as for post‐hoc analysis of the lesion site in fixed tissue, which can be correlated with the live imaging phase. © 2015 by John Wiley & Sons, Inc.